Stratigraphy and geological structure of the Lavrion area (Attica, Greece) - PHOTIADES, A.; CARRAS, N. (Bulletin of the Geological Society of Greece, 2001)
The geological mapping of the Lavrion area lead to a revision of the lithostratigraphic subdivision and the recognition of three superposed tectonic units. The lower unit, the so-called autochthonous system, consists of a Triassic - Jurassic metamorphic Pelagonian series, a disconformity related to the Eohellenic orogenic phase, and a Tithonian - Lower Cretaceous non-metamorphic transgressive cover. Upon the lower unit, the "phyllite" nappe lies (middle unit), having on the top some remnants of a non-metamorphic Pelagonian nappe (upper unit).